Autologous Graft Thickness Affects Scar Contraction and Quality in a Porcine Excisional Wound Model. Issue 7 (July 2015) - Chan, Rodney K.; Rose, Lloyd F.; Wu, Jesse C.; Tucker, David I.; Chan, Maren M.; Christy, Robert J.; Hale, Robert G.; Leung, Kai P.
Abstract : Background: Texture, color, and durability are important characteristics to consider for skin replacement in conspicuous and/or mobile regions of the body such as the face, neck, and hands. Although autograft thickness is a known determinant of skin quality, few studies have correlated the subjective and objective characters of skin graft healing with their associated morphologic and cellular profiles. Defining these relationships may help guide development and evaluation of future skin replacement strategies. Methods: Six-centimeter-diameter full-thickness wounds were created on the back of female Yorkshire pigs and covered by autografts of variable thicknesses. Skin quality was assessed on day 120 using an observer scar assessment score and objective determinations for scar contraction, erythema, pigmentation, and surface irregularities. Histological, histochemical, and immunohistochemical assessments were performed. Results: Thick grafts demonstrated lower observer scar assessment score (better quality) and decreased erythema, pigmentation, and surface irregularities. Histologically, thin grafts resulted in scar-like collagen proliferation while thick grafts preserves the dermal architecture. Increased vascularity and prolonged and increased cellular infiltration were observed among thin grafts. In addition, thin grafts contained predominately dense collagen fibers, whereas thick grafts had loosely arranged collagen. α-Smooth muscle actin staining for myofibroblasts was observed earlier and persisted longer among thinner grafts. Conclusions: Graft thickness is an important determinant of skin quality. High-quality skin replacements are associated with preserved collagen architecture, decreased neovascularization, and decreased inflammatory cellular infiltration. This model, using autologous skin as a metric of quality, may give a more informative analysis of emerging skin replacement strategies.